Smart Supervision for School Empowerment and Educational Performance Improvement: A Study in Saudi Public Education - Al-Luhaidan, Maryam Abdullah; Al-Otaibi, Mashael Aseer (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the current state and inherent challenges of educational supervision in Saudi public schools, identify the prospective roles of Smart Supervision as a strategic approach for school empowerment, improving pedagogical performance, and fostering self-accountability. It also sought to determine the requirements and anticipated challenges for its effective activation, and to propose implementation strategies aligned with Saudi Vision 2030. The research employed a descriptive-analytical methodology using a questionnaire as the primary data collection instrument from a convenience sample of (70) educational practitioners (teachers, supervisors, principals, and deputies). Data analysis utilized the statistical program (SPSS). Results indicated that traditional educational supervision practices face numerous challenges. Conversely, there was a very high consensus on the positive prospective roles of Smart Supervision in school empowerment (Mean = 4.40), improving performance, and addressing traditional supervision shortcomings. Essential requirements for implementation were identified, notably specialized training (Mean = 4.64) and robust technical infrastructure, alongside organizational and human resource challenges. The sample showed very high support for initiating Smart Supervision as a pilot project (Mean = 4.49) before widespread generalization. The study concluded that Smart Supervision represents a strategic approach for developing the supervisory system in light of the digital transformation and Vision 2030, recommending capacity building, necessary support, clear activation policies, and the crucial importance of launching pilot projects to ensure successful nationwide implementation across the Kingdom of Saudi Arabia.
Keywords: Artificial Intelligence; School Empowerment; Public Education; Digital Transformation; Educational Supervision; Kingdom of Saudi Arabia